2019
DOI: 10.1371/journal.pone.0220899
|View full text |Cite
|
Sign up to set email alerts
|

Users’ and therapists’ perceptions of myoelectric multi-function upper limb prostheses with conventional and pattern recognition control

Abstract: Objective To describe users’ and therapists’ opinions on multi-function myoelectric upper limb prostheses with conventional control and pattern recognition control. Design Qualitative interview study. Settings Two rehabilitation institutions in the Netherlands and one in Austria. Subjects The study cohort consisted of 15 prosthesis users (13 males, mean age: 43.7 years, average experience with multi-function prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 32 publications
1
64
2
Order By: Relevance
“…Whereas qualitative research has been limited and conducted in the context of less intimately integrated limb prostheses (Murray, 2004;Lundberg et al, 2011;Widehammar et al, 2018;Cuberovic et al, 2019;Franzke et al, 2019;Graczyk et al, 2019;Hansen et al, 2019), it has nevertheless shown that the perspectives and opinions of those impacted by such medical interventions form a particular kind of evidence and expertise (Murray, 2004). The embodied knowledge (Merleau-Ponty, 1962;Bourdieu, 1990) produced from firsthand experience is unique from data gathered from traditional quantitative methods, serving to complement and at times even challenge quantitative data.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas qualitative research has been limited and conducted in the context of less intimately integrated limb prostheses (Murray, 2004;Lundberg et al, 2011;Widehammar et al, 2018;Cuberovic et al, 2019;Franzke et al, 2019;Graczyk et al, 2019;Hansen et al, 2019), it has nevertheless shown that the perspectives and opinions of those impacted by such medical interventions form a particular kind of evidence and expertise (Murray, 2004). The embodied knowledge (Merleau-Ponty, 1962;Bourdieu, 1990) produced from firsthand experience is unique from data gathered from traditional quantitative methods, serving to complement and at times even challenge quantitative data.…”
Section: Introductionmentioning
confidence: 99%
“…Actual EMG prosthetic hands require some different movements done by the user to choose a specific movement manipulation as well as the pressure applied to the object surface [ 30 ]. This specific movement as multiple muscle contractions in a short time are sometimes not well accepted by the users [ 31 ]. To correctly control the force applied to the objects and the adequate fingers movement, the prosthetic hand requires the use of force sensitive sensors applied to all fingers individually.…”
Section: Resultsmentioning
confidence: 99%
“…ML control can reveal the full potential of multiarticulate hands, as the clinical standard two-site “Direct Control” (DC) scheme is currently one of the main limiting factors in prosthetic control. In contrast to DC, ML control does not require isolated subsequent electromyographic (EMG) signals derived from two electrodes to control all available grip modes, but utilizes more intuitive control generated by patterns of muscle contractions [ 9 ]. However, ML control currently suffers from robustness issues while DC is faster in tasks that only require one degree of freedom (DoF) [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%